Language across Culture and Curriculum - Sharma, Neha (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Such an interesting topic 'Language across Culture and Curriculum'. We have seen so many times people debating and discussing about the culture of a Nation. We talk a lot on the above mentioned topic about the beauty and diversity of the culture we are born and brought up in. We all love to share the complexities and complementariness of our culture with people living across the borders. The beauty of the spread of the bhavas of expressing one owns culture defines for who he is. Language is not only about what we speak but its extension is much more beyond that. Verbal communication is not only the communication which we uses to communicate but it‘s better to say that it is one of the form of the language to express one owns feeling via different mode. Chaptering the language in curriculum form can be considered as putting barricading to the expression. It‘s not possible to give periphery to the language by just framing it into a exchange of culture or giving it a curriculum. Language what we speak is now a days is completely globalized and if not being able to speak but still one can exchange and convey what he or she wants to. Language needs no barrier of borders, people standing with newly designed machine guns and not letting anyone in within their area. It is something which floats across all the man-made barriers and conveys what it has to.